2015
DOI: 10.1111/njb.00859
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphology of fruits and seeds of Iranian Geranium (Geraniaceae), and its systematic significance

Abstract: The fruit and seed micromorphology of 22 species of Geranium, representing the eight sections of the genus represented in Iran (G. sectt. Dissecta, Geranium, and Tuberosa of subgen. Geranium; sectt. Batrachioidea, Divaricata, Lucida, Ruberta and Trilopha of subgen. Robertium), have been examined by scanning electron microscopy (SEM). Macro‐ and micromorphological characters, including fruit and seed shape, size, color, hair type and density, mericarp ornamentations, hilum position, seed coat pattern, epidermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Previous study on species delimitation and species relationship performed in this genus (Salimi Moghadam et al 2015) revealed that fruit characters are important for separating taxa at infrageneric rank and their results show that the species can be separated into subgenera and sections based on fruit morphology, while seed micromorphological features generally do not support the sectional taxonomy, but provide valuable characters for the delimitation at species groups, species, and infraspecific levels (Salimi Moghadam et al 2015). Studies on Geranium species are mainly dealing with taxonomy, seed and pollen morphology, stem and leaf anatomy (Esfandani Bozchaloyi et al 2017a, b, c, d, Keshavarzi et al 2015, Onsori et al 2010, Salimi Moghadam et al 2015, Salimpour et al 2009, but there are no attempt to study genetic diversity, ecological adaptation and intra-and interspecific differentiation along with morphometric studies on Geranium of Iran. Therefore, we performed morphological and molecular study of 10 collected species of 5 sections in the subg.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study on species delimitation and species relationship performed in this genus (Salimi Moghadam et al 2015) revealed that fruit characters are important for separating taxa at infrageneric rank and their results show that the species can be separated into subgenera and sections based on fruit morphology, while seed micromorphological features generally do not support the sectional taxonomy, but provide valuable characters for the delimitation at species groups, species, and infraspecific levels (Salimi Moghadam et al 2015). Studies on Geranium species are mainly dealing with taxonomy, seed and pollen morphology, stem and leaf anatomy (Esfandani Bozchaloyi et al 2017a, b, c, d, Keshavarzi et al 2015, Onsori et al 2010, Salimi Moghadam et al 2015, Salimpour et al 2009, but there are no attempt to study genetic diversity, ecological adaptation and intra-and interspecific differentiation along with morphometric studies on Geranium of Iran. Therefore, we performed morphological and molecular study of 10 collected species of 5 sections in the subg.…”
Section: Introductionmentioning
confidence: 99%
“…Several taxonomic studies have shown that seed and trichome micromorphology can be useful for classification and delimitation of taxa at all taxonomic levels and in different plant families (Barthlott 1981, Krak and Mraz 2008, Salmaki et al 2009, Satil et al 2011, Salimi Moghadam et al 2015, Tavakkoli and Assadi 2016, Arabi et al 2017. A high diversity of trichomes on the gynocium and carpels has been shown to provide valuable information for identifying Glaucium species (Boissier 1867, Cullen 1966, Mory 1979.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed importance of fruit micro‐morphological characteristics used in taxonomy of the genus. Fruit characters were found to be important for separating taxa at infra‐generic level but are not efficient to differentiate the sections (Salimi Moghadam et al, ). However, seed morphology was found useful for the taxonomic delimitation at the generic, specific as well as at the infra‐specific levels (Ather et al, ).…”
Section: Introductionmentioning
confidence: 99%